KONTRIBUSI KONSEP DIRI FISIK DAN MOTIVASI BERPRESTASI TERHADAP PERENCANAAN KARIER SISWA KELAS XI SMKN SE-KOTA PEKANBARU - Arlizon, Raja; Saam, Zulfan; Donal, Donal (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2018)
The general objective of this research is to describe: (a) Level of physical self-concept boys and girls (b) The level ofstudent achievement motivationof men and women,(c) Career planning level boys and girls, (d) Differences in physical self-concept, achievement motivation and career planning boy swith girls, (e) Contribution of physical self-concept and achievement motivation to get her to career planning under taken inclass XI SMKN Se-kota Pekanbaru. This study uses a quantitative approach with correlation and comparative methods by making proportional random sampling technique. In this study the following conclusions can be adduced: (a) Physical self-concept level boys and girls in general are in the medium category, (b) The level of student achievement motivation of men and women in general are in the category of being, (c) Level career planning to ward boys and girls in general are at a high category, (d) There are differences in physicalself-concept of boysandgirls, (e) There were no differences in achievement motivation and career planning boys and the women, (f) There contribution of physical self-concept and a chievement motivation on student career planning direction.